Exploring Heterogeneous Mobile Architectures with a High-Level Programming Model - Carvalho, Wilson de; Andrade, Guilherme; Caldeira, Pedro; Utsch, Renato; Ferreira, Renato Antônio Celso; Rocha, Leonardo; Carvalho, Renan; Násser, Millas (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD); 2017: Anais do XXIX International Symposium on Computer Architecture and High Performance Computing, 2017)
The development of new technologies is setting a new era characterized, among other factors, by the rise of sophisticated mobile devices containing CPUs and GPUs. This emerging scenario of heterogeneous mobile architectures brings challenging issues regarding the use of the available computing resources. Such issues are mainly related to the intrinsic complexity of coordinating these processors in order to increase application performance. In this sense, this paper presents a high-level programming model to implement parallel patterns that can be executed in a coordinate way by heterogeneous mobile architectures. A comparative analysis of performance and programming complexity is presented, contrasting code generated automatically from the proposed programming model with low-level manually-optimized implementations.